Evaluasi Dampak Pembatasan Pergerakan (Belok Kanan) terhadap Kinerja Simpang Jl. Karimata sampai Jl. Putri Daranante - Ardian Pratama; Said Said; Eti Sulandari (Jurnal Sains dan Teknologi, 2026)
Right-turn prohibition is one of the traffic management and engineering measures aimed at reducing traffic conflict points and improving intersection performance. This study aims to evaluate the impact of the right-turn restriction at the unsignalized intersection of Jalan Karimata–Jalan Putri Daranante, Pontianak City, based on the Indonesian Road Capacity Guidelines (PKJI) 2023. A descriptive quantitative method was employed using traffic survey and CCTV data collected on a weekday, weekend, and holiday. The evaluation focused on the restriction period by comparing three conditions: the existing condition (the actual situation while the policy is enforced), Scenario 1 (the condition before the policy was implemented), and Scenario 2 (the condition assuming full compliance with the restriction). The analyzed parameters included capacity, degree of saturation, delay, queue probability, and level of service. During the critical period on Monday (06:30–07:30) with a traffic volume of 1,308 pcu/h, the existing condition and Scenario 1 produced nearly identical performance (capacity of 2,437 and 2,435 pcu/h; degree of saturation of 0.54; delay of 9.86 s/pcu; queue probability of 13–27%), indicating that the enforced policy has not yet produced a meaningful change. In contrast, Scenario 2 showed an increase in capacity to 2,682 pcu/h, a decrease in the degree of saturation to 0.49, delay to 9.37 s/pcu, and queue probability to 11–24%. The level of service remained at category B across all three conditions. The findings indicate that the effectiveness of the right-turn restriction is strongly influenced by road users' compliance.